2021
DOI: 10.1111/mec.15871
|View full text |Cite
|
Sign up to set email alerts
|

Low dispersal and ploidy differences in a grass maintain photosynthetic diversity despite gene flow and habitat overlap

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(54 citation statements)
references
References 104 publications
4
43
0
Order By: Relevance
“…The C 4 metabolism relies on a biochemical cycle operating within a specialized leaf anatomy, which concentrates CO 2 around Rubisco, suppressing the energetically-costly photorespiratory pathway (Hatch 1987). The C 4 trait is highly polyphyletic, but its multiple origins Southern Africa, genetic analyses have shown that natural hybrids are rare (Olofsson et al 2016;Bianconi et al 2020;Olofsson et al 2021). The lack of a clear hybrid zone has been partially explained by the differences in ploidy levels among photosynthetic types where they are found in sympatry (Olofsson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The C 4 metabolism relies on a biochemical cycle operating within a specialized leaf anatomy, which concentrates CO 2 around Rubisco, suppressing the energetically-costly photorespiratory pathway (Hatch 1987). The C 4 trait is highly polyphyletic, but its multiple origins Southern Africa, genetic analyses have shown that natural hybrids are rare (Olofsson et al 2016;Bianconi et al 2020;Olofsson et al 2021). The lack of a clear hybrid zone has been partially explained by the differences in ploidy levels among photosynthetic types where they are found in sympatry (Olofsson et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Alloteropsis semialata has a paleotropical distribution, with C 3 and C 3 +C 4 populations in Southern and Central/Eastern regions of Africa, respectively, and C 4 individuals occurring across Africa, South and Southeast Asia, and Oceania (Lundgren et al 2015; Olofsson et al 2016; Bianconi et al 2020; Olofsson et al 2021). The photosynthetic types in A. semialata are associated with distinct genetic lineages (Lundgren et al 2015; Olofsson et al 2016), which initially diverged around 3 Mya (Bianconi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted April 18, 2021. ; https://doi.org/10.1101/2021.04.16.440116 doi: bioRxiv preprint angusta individuals, and 15 newly sequenced A. semialata, which were combined with 49 previously sequenced A. semialata (Olofsson et al, 2021;Table S1).…”
mentioning
confidence: 99%